Watching YouTube : extraordinary videos by ordinary people - Strangelove, Michael (Toronto ; Buffalo [N.Y.] : University of Toronto Press, 2010)
Michael Strangelove provides a broad overview of the world of amateur online videos and the people who make them. He describes how online digital video is both similar to and different from traditional home-movie-making and argues that we are moving into a post-television era characterized by mass participation. --from publisher description
Home movies in a global village -- The home and family on YouTube -- Video diaries: the real you in YouTube -- Women of the 'Tube -- The YouTube community -- The YouTube wars: politics, religion, and armed conflict -- The post-television audience.
Includes bibliographical references (p. [223]-246) and indexes.
Keywords: YouTube (Electronic resource); Internet videos -- Social aspects; Online social networks -- Social aspects; Mass media and culture